Nipah virus: a recently emergent deadly paramyxovirus - Chua, K.B.; Bellini, W.J.; Rota, P.A.; Harcourt, B.H.; Tamin, A.; Lam, S.K.; Ksiazek, T.G.; Rollin, P.E.; Zaki, S.R.; Shieh, W.; Goldsmith, C.S.; Gubler, D.J.; et al. (American Association for the Advancement of Science, 2000)
A paramyxovirus virus termed Nipah virus has been identified as the etiologic agent of an outbreak of severe encephalitis in people with close contact exposure to pigs in Malaysia and Singapore. The outbreak was first noted in late September 1998 and by mid-June 1999, more than 265 encephalitis cases, including 105 deaths, had been reported in Malaysia, and 11 cases of encephalitis or respiratory illness with one death had been reported in Singapore. Electron microscopic, serologic, and genetic studies indicate that this virus belongs to the family Paramyxoviridae and is most closely related to the recently discovered Hendra virus. We suggest that these two viruses are representative of a new genus within the family Paramyxoviridae. Like Hendra virus, Nipah virus is unusual among the paramyxoviruses in its ability to infect and cause potentially fatal disease in a number of host species, including humans.